Pontiac fever: an operational definition for epidemiological studies - Mathieu Laurence; Hartemann Philippe; Zmirou-Navier Denis; Deloge-Abarkan Magali; Tossa Paul (BMC, 2006)
Abstract Background Pontiac fever is usually described in epidemic settings. Detection of Pontiac fever is a marker of an environmental contamination by Legionella and should thereby call for prevention measures in order to prevent outbreak of Legionnaire's disease. The objective of this study is to propose an operational definition of Pontiac fever that is amenable to epidemiological surveillance and investigation in a non epidemic setting. Methods A population of 560 elderly subjects residing in 25 nursing homes was followed during 4 months in order to assess the daily incidence of symptoms associated, in the literature, with Pontiac fever. The water and aerosol of one to 8 showers by nursing home were characterized combining conventional bacterial culture of Legionella and the Fluorescence In Situ Hybridization (FISH) technique that used oligonucleotides probes specific for Legionellaceae. A definition of Pontiac fever was devised based on clinical symptoms described in epidemic investigations and on their timing after the exposure event. The association between incidence of Pontiac fever and shower contamination levels was evaluated to test the relevance of this definition. Results The proposed definition of Pontiac fever associated the following criteria: occurrence of at least one symptom among headache, myalgia, fever and shivers, possibly associated with other 'minor' symptoms, within three days after a shower contaminated by Legionella, during a maximum of 8 days (minimum 2 days). 23 such cases occurred during the study (incidence rate: 0.125 cases per person-year [95% CI: 0.122-0.127]). A concentration of Legionella in water equal to or greater than 104.L-1 (FISH method) was associated with a significant increase of incidence of Pontiac fever (p = 0.04). Conclusion Once validated in other settings, the proposed definition of Pontiac fever might be used to develop epidemiological surveillance and help draw attention on sources of Legionella.